Analisis Penyebab Rendahnya Kemampuan Pemecahan Masalah Calon Guru Matematika Menggunakan APKL, USG, dan Diagram Fishbone - Darmawan, Puguh; Yohanes, Barep; Hadi, Mei Rina (Jurnal Tadris Matematika, 2023)
Problem-solving is one of the process standards that has been discussed by NCTM and is very important for prospective mathematics teachers to master. The reality is that prospective mathematics teachers have low problem-solving abilities, so it is necessary to analyze the causes of these low-solving abilities. This research aims to uncover the causes of the low problem-solving abilities of prospective mathematics teachers using PKL, USG, and fishbone diagrams. The research method used is qualitative. The research subjects were students of the Mathematics Education study program, FMIPA, Universitas PGRI Banyuwangi who were prospective mathematics teachers according to the achievements of study program graduates. The main instrument of this research is the researcher. Meanwhile, supporting instruments include tests, open questionnaires, researcher notes, interviews, and documentation. Data analysis was carried out using the APKL, followed by the USG method, and then using the fishbone diagram. The results of the research reveal that the causes of low problem-solving abilities are inadequate procedural abilities in solving mathematical problems, inadequate declarative knowledge or knowledge of mathematical concepts, inadequate representational abilities, biological problems, and inadequate interests. This research provides signs for educators to anticipate the causes of the low problem-solving abilities of prospective mathematics teachers.